International Sports Events Organization and Execution as an Object of Legal Regulation - Vyacheslav A. Tutinas (Evropejskij Issledovatelʹ, 2012)
The contribution is focused on the international sports events organization and execution as an object of legal regulation, studies its structure and the degree of impact on the parameters of legal regulation.